Grief can bring life: Bioethical reflections on the field of transplantation - Zanni, Anastasia (Bioethica, 2022)
Human organ transplantations, either from live or from dead donors, with the first successful procedure performed in 1954 by Joseph Murray’s surgical team, is one of the most important achievements of medical science during the 20th century, comparable perhaps, only by the discovery of penicillin by Fleming in 1928 and the vaccine against poliomyelitis by Salk in 1955. In our country, the first successful kidney transplantation was performed in Thessaloniki, in 1968. In this literature review a series of aspects will be presented regarding the dynamics and prospects of human organ transplantations in Greece. Unfortunately, in contrast to many other countries in Europe and America, where there is a gradual increase in the numbers of human organ transplantations, the data from Greece are not far from being characterized as disappointing, with the donor index (donors per million population) being at the level of 4.7, while the European average is above 20. The reasons for these poor performances are many – among them the long-standing problems of trust that the Greek society has in organ transplant procedures, the poor support of the media, the minimal participation of the various levels of the education, the significant infrastructure, and staff shortages and, of course, more recently, the COVID-19 pandemic, which has adversely affected the global transplant activity. To address those negative facts, it is necessary to take immediate targeted actions, including the continuous information of the public and the continuing training and modernization of the scientific and the material resources in all the general hospitals of the country. The introduction of the bioethical mediator as an institutional role in our country plays an important role towards this goal. Using their specialized knowledge, they will be able to solve many of the legal and ethical dilemmas which arise daily in the complex context of organ transplantation, which the health professionals are not sufficiently trained and qualified to deal with.